Probing the relationship between BTBD9 and MEIS1 in C. elegans and mouse - Shangru Lyu; Atbin Doroodchi; Yi Sheng; Mark P. DeAndrade; Youfeng Yang; Yuning Liu; Michael A. Miller; Rui Xiao; Yuqing Li; Michael Nevels (Experimental Results, 2020)
Restless legs syndrome (RLS) is a neurological disorder characterized by an urge to move and uncomfortable sensations. Genetic studies have identified polymorphisms in up to 19 risk loci, including MEIS1 and BTBD9. Rodents deficient in either homolog show RLS-like phenotypes. However, whether MEIS1 and BTBD9 interact in vivo is unclear. Here, with C. elegans, we observed that the hyperactive egg-laying behavior caused by loss of BTBD9 homolog was counteracted by knockdown of MEIS1 homolog. This was further investigated in mutant mice with Btbd9, Meis1, or both knocked out. The double knockout mice showed an earlier onset of the motor deficit in a wheel running test but did not have increased sensitivity to heat stimuli as observed in single knock outs. Meis1 protein level was not influenced by Btbd9 deficiency, and Btbd9 transcription was not affected by Meis1 haploinsufficiency. Our results demonstrate that MEIS1 and BTBD9 do not regulate each other.